Single-cell transcriptomics reveals a role for pancreatic duct cells as potential mediators of inflammation in diabetes mellitus - Muñoz García, Amadeo; Juksar, Juri; Groen, Nathalie; Zaldumbide, Arnaud; de Koning, Eelco; Carlotti, Françoise (Frontiers in Immunology, 2024)
Inflammation of the pancreas contributes to the development of diabetes mellitus. Although it is well-accepted that local inflammation leads to a progressive loss of functional beta cell mass that eventually causes the onset of the disease, the development of islet inflammation remains unclear. Here, we used single-cell RNA sequencing to explore the cell type-specific molecular response of primary human pancreatic cells exposed to an inflammatory environment. We identified a duct subpopulation presenting a unique proinflammatory signature among all pancreatic cell types. Overall, the findings of this study point towards a role for duct cells in the propagation of islet inflammation, and in immune cell recruitment and activation, which are key steps in the pathophysiology of diabetes mellitus.